Effect of the ionic radius on structural properties of orthochromites RCrO3 (R = La, Gd, Y) (Acta Scientiarum. Technology, 2021)
The main objective of this work was to detail out how to obtain important parameters in the structural analysis of materials with perovskite structure in order to help beginning researchers in this area. In particular, a thorough comparative and investigative study of the effect of ionic radius on the structural properties of orthochromites RCrO3 (R = La, Gd, Y) were presented. It is observed that the b and c lattice parameters increased, whereas a lattice parameter decreased as the ionic radius increased. Consequently, an increase in the unit-cell volume and tolerance factor was observed. The angles and bond lengths increased with an increase in the ionic radius, albeit the inclination angle, as well as the rotation angle, tends to decrease. The distortion parameter suffered a fluctuation in its value according to the increasing ionic radius. Lastly, Williamson-Hall (W-H) analysis caused a decrement in the strain according to decreasing ionic radius.